2021
DOI: 10.1039/d1gc00198a
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable plasma-catalytic bubbles for hydrogen peroxide synthesis

Abstract: Hydrogen peroxide (H2O2) is a green oxidant widely used in various fields, from water treatment to rocket propellant. Currently, H2O2 is predominantly manufactured via the anthraquinone process, which requires large...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 64 publications
1
41
0
Order By: Relevance
“…Previous studies have confirmed that hydrogen peroxide ( ) is a key factor in the plasma reduction process of [ 23 , 25 ]. is a long-lived species that is generated through several pathways [ 35 , 36 , 37 ]. In the plasma jet, gaseous formed inside the quartz tube is delivered through the nozzle, and aqueous is generated continuously at the gas−liquid interface and accumulated inside the bulk liquid, resulting in a high concentration of .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have confirmed that hydrogen peroxide ( ) is a key factor in the plasma reduction process of [ 23 , 25 ]. is a long-lived species that is generated through several pathways [ 35 , 36 , 37 ]. In the plasma jet, gaseous formed inside the quartz tube is delivered through the nozzle, and aqueous is generated continuously at the gas−liquid interface and accumulated inside the bulk liquid, resulting in a high concentration of .…”
Section: Resultsmentioning
confidence: 99%
“…In the plasma jet, gaseous formed inside the quartz tube is delivered through the nozzle, and aqueous is generated continuously at the gas−liquid interface and accumulated inside the bulk liquid, resulting in a high concentration of . In the gas phase, plasma-generated radicals can recombine to form gaseous , which can be transported to the gas–liquid interface (Equation (1)) [ 35 ]. was observed at all positions along the plasma jet, as shown in Figure 4 B.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations